Dehydration of water/pyridine mixtures by pervaporation using cellulose acetate/ polyacrylonitrile blend membrane - Lv, J H (Water science and technology : a journal of the International Association on Water Pollution Research, 2011)
Cellulose acetate/ polyacrylonitrile (CA/PAN) membranes were prepared and used to separate pyridine / water mixtures by pervaporation. The membranes were characterized through SEM. The effects of feed concentration, operation temperature and downstream pressure on the separation performance were evaluated. Experimental results indicated the increase of operation temperature could raise the permeation flux and the separation factor, while increasing feed concentration and downstream pressure would raise the separation factor and decrease the permeation flux. Under the conditions that pyridine solution was 99 wt.%, operation temperature was 323 K and downstream pressure was 20 mmHg, the CA/PAN blend membrane showed its best separation performance that the permeation flux was 56.g.m-2 h-1 and the separation factor was 182